Description of Maternal Knowledge in Exclusive Breastfeeding on Pandemic Covid 19 in 2020 - Tiara Pratiwi; Nelly Mariyam; Mardelia Astriani (Jurnal Kesehatan Masyarakat Celebes, 2022)
The importance of exclusive breastfeeding has not been widely realized by many parties. This can be seen from the 2010 Susenas (National Socio-Economic Survey) data that only 33.6 percent of infants aged 0-6 months receive exclusive breastfeeding. Based on the 2010 Basic Health Research (Riskesdas), only 15.3 percent of babies aged less than 6 months are exclusively breastfed. Mothers do not fully understand the correct way of breastfeeding including the techniques and methods of obtaining breast milk, especially for working mothers, which are an obstacle to exclusive breastfeeding (Roesli, 2008). There are still many obstacles experienced in the implementation of exclusive breastfeeding, where the conditions of the pandemic Covid 19 which began to worsen in early 2020, although until now the transmission of the COVID-19 virus through breast milk and breastfeeding has not been proven. The study was conducted to describe the knowledge of mothers about exclusive breastfeeding during the Covid Pandemic 19. The type of research used is descriptive-analytic research with a quantitative approach to describe all objects and research subjects using accidental sampling technique where the sample is the entire population of 67 mothers. breastfeeding. The instrument used was primary data collection by using a questionnaire. The results showed that 67 respondents who had good knowledge were 22 respondents (32.8%), 39 respondents (58.2%) had sufficient knowledge and 6 respondents (9%) had insufficient knowledge. The number of mother respondents who have good knowledge tends to provide exclusive breastfeeding. Based on data from the results of cross tabulation (crosstab), it shows that the number of respondents who have good knowledge and provide exclusive breastfeeding is 17 people (25.3%), while respondents who are knowledgeable enough and give exclusive breastfeeding are 25 people (37.3%) and respondents only 6 people (4.6%) had less knowledge and exclusive breastfeeding. However, all breastfeeding mothers do not know that mothers with suspected Covid 19 or mothers who are independently isolated can still provide breast milk by following health protocols to prevent transmission of Covid 19.